ALTERNATIF PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU TINDAK PIDANA KORUPSI DENGAN KERUGIAN KEUANGAN NEGARA BERJUMLAH KECIL - Anugerah, Listakeri S.; Kristiawanto, Kristiawanto; Ismed, Mohamad (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Alternative criminal liability that can be provided to the perpetrators of corruption in the event of State losses caused by a small amount but meeting some of the characteristics presented by the researcher. In Indonesia, there have been many examples of corruption cases where the state's financial losses are small, but they are still continued to trial. The imposition of imprisonment on perpetrators of corruption is currently considered no longer effective in providing a deterrent effect on the perpetrators. Basically, the victim of corruption is the state. The state which in this case experiences losses of state assets makes the state the sole victim who must be given justice as a manifestation of the purpose of the law. The state as a victim with the result of the loss of state assets, in the long term also causes misery for the community. The method used in this study This study uses descriptive analytical research, which is carried out with the main aim of providing an objective picture or description of a situation. With a statute approach, case approach, conceptual approach, analytical approach, normative juridical approach. The research results recommend alternative responsibilities that will be imposed on perpetrators of corruption crimes amounting to small state financial losses as long as they meet the classifications that have been studied by the Researcher. The results of this study that on the impact of corruption practices on a small scale on the quality of handling cases for law enforcement and the quality of sentencing the perpetrators, as well as the recovery of State losses so that the state that has been harmed as a victim regain their rights that have been taken away by the perpetrators. Through the analysis of the literature and the study of several cases presented by the author, this thesis also identifies common patterns that occur, causal factors, as well as suggestions for handling them.